Understanding Repurchase Intention in E-Commerce: Evidence from Tokopedia Users in Kalimantan - Della Olivia Caterina Kalangit; Suramli; Armini Ningsih (International Journal of Management, Economic and Accounting, 2026)
This study examines the effects of utilitarian value, convenience, familiarity, and experience on repurchase intention through trust and satisfaction among Tokopedia users in Kalimantan. A quantitative research approach was employed using data collected from 112 respondents. The data were measured using a five-point Likert scale and analyzed through path analysis using IBM SPSS Statistics 23 and Structural Equation Modeling (SEM) using IBM AMOS 5. The analysis included validity and reliability testing, parameter estimation, and structural model fit assessment. The findings indicate that convenience and experience significantly influence trust, while familiarity and utilitarian value do not significantly affect trust. Furthermore, familiarity, experience, and trust significantly influence satisfaction, whereas utilitarian value and convenience do not have significant effects on satisfaction. Regarding repurchase intention, familiarity, experience, trust, and satisfaction have significant effects, while utilitarian value and convenience do not have significant direct effects. These findings indicate that consumers’ continued purchasing decisions in online marketplaces are shaped more strongly by their accumulated experience, familiarity with the platform, trust, and satisfaction than by functional value and convenience alone. The study contributes to the understanding of consumer repurchase behavior in digital marketplaces by highlighting the mediating roles of trust and satisfaction in linking consumer experiences with repurchase intention. The findings provide practical implications for online marketplace managers in developing strategies that strengthen consumer trust, satisfaction, and long-term purchasing relationships.